2006
DOI: 10.1590/s0074-02762006000900009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of schistosomiasis, through school surveys, in the Forest Zone of Pernambuco, Brazil

Abstract: This work had the objective of assessing the present epidemiological situation regarding schistosomiasis through performing Kato-Katz coproscopic tests on representative samples of schoolchildren from each of the 43 municipality of endemic area of the state of Pernambuco, Brazil. The methodology is recommended by the World Health Organization to conduct sampled surveys among children at elementary school levels, ideal target group for baseline surveys: (i) schools are accessible; (ii) the greatest prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
(12 reference statements)
2
27
2
6
Order By: Relevance
“…Such techniques minimize the problems of precision and validity, and can be easily executed by the PCE-SUS. A recent study involving school surveys among 9-12 yrs old children in all 43 municipalities of the ZMP (Barbosa et al 2006b) identified 25 (58%) of them in the moderate prevalence class and the remaining, in the low prevalence one. Surveys based on representative samples enable not only to know the real situation of schistosomiasis but also to suggest adequate control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Such techniques minimize the problems of precision and validity, and can be easily executed by the PCE-SUS. A recent study involving school surveys among 9-12 yrs old children in all 43 municipalities of the ZMP (Barbosa et al 2006b) identified 25 (58%) of them in the moderate prevalence class and the remaining, in the low prevalence one. Surveys based on representative samples enable not only to know the real situation of schistosomiasis but also to suggest adequate control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Inquéritos realizados em escolares na faixa etária de 9 a 12 anos, residentes em municípios situados na Zona da Mata do estado, região de localização dos municípios das RS II e III, demonstraram a ocorrência de transmissão recente da parasitose nessa área. 14,15 No inquérito realizado por Barbosa 14,15 em 2005, quase metade (45,5%) dos municípios localizados na área que compõe a RS II apresentou positividade considerada moderada (10 a 50%) para esquistossomose e a grande maioria (73%) dos municípios localizados na área correspondente à RS III apresentou a mesma positividade. Os resultados apresentados neste trabalho mostram concordância com os resultados dos estudos supracitados e reforçam a permanência da Zona da Mata de Pernambuco como a área de maior transmissão da doença, apresentando a RS III como a de maior positividade nos anos analisados, seguida pela RS II.…”
Section: Regional V Pernambucounclassified
“…Even though various surveys and studies over the last 30 years have shown occurrences of schistosomiasis and geohelminthiasis in the ZMP 7,8,14,15 no preventive measures are known to have been effective in the endemic area for decreasing the numbers of cases and morbidity due to these health hazards among schoolchildren in the ZMP. …”
Section: Poso�vity For S Mansoni (%) Infec�on Intensity For S Mansomentioning
confidence: 99%
“…In a survey conducted by Barbosa et al 8 in the ZMP, it was shown that there was an accumulated prevalence of schistosomiasis of 14.4%, and that for geohelminthiasis the prevalence was over 50% in some municipalities, thus proving that these parasites are a relevant public health issue in this state. Hence, the present study aimed to spatially assess occurrences of schistosomiasis and geohelminthiasis in the ZMP, using GIS as an auxiliary tool, with the intention of showing the epidemiological landscape of occurrences of these parasitoses, as a support for planning and applying effective prevention and control measures.…”
Section: Introductionmentioning
confidence: 97%